Hakikat Manusia dan Implikasinya Terhadap Pendidikan Islam - auliaz, isma (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2023)
This article was written with the aim of knowing how the true nature of human beings. In writing this article, the author uses a descriptive method (library research) or known as literature review. The sources we took came from several other articles as well as printed books. With this article, the author will answer several problem formulations, namely how the concept of human creation, how the process of human creation, what is the purpose of human creation, what is the function of human creation, and how the implications of human creation on Islamic education. It is important for us to first recognize humans as objects of Islamic education studies so that Islamic education applied can be appropriate and can balance human functions as creatures, educators and students, as well as servants of Allah and the caliph of Allah. That way human identity as human kamil or kaffah Muslims can be said to be perfect.